a³-b³= (a-b)(a²+ab+b²)
(5-y)(25+5y+y²)
(5 - у)(25 + 5у + у²)
Пошаговое объяснение:
125 - у³ = 5³ - у³ - разность кубов двух чисел, которая равна произведению разности этих чисел и неполного квадрата их суммы:
a³ – b³ = (a – b) (a² + ab + b²)
5³ - у³ = (5 - у)(5² + 5у + у²) = (5 - у)(25 + 5у + у²)
a³-b³= (a-b)(a²+ab+b²)
(5-y)(25+5y+y²)
(5 - у)(25 + 5у + у²)
Пошаговое объяснение:
125 - у³ = 5³ - у³ - разность кубов двух чисел, которая равна произведению разности этих чисел и неполного квадрата их суммы:
a³ – b³ = (a – b) (a² + ab + b²)
5³ - у³ = (5 - у)(5² + 5у + у²) = (5 - у)(25 + 5у + у²)